If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2x + -4 = 0 Reorder the terms: -4 + x + -2x = 0 Combine like terms: x + -2x = -1x -4 + -1x = 0 Solving -4 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4
| 20(x-0.5)=70 | | 26-18=2(x-2) | | 540-8P=120+6P | | 4(8a+-8)= | | 8z=12 | | 2x-sin(0.5x)=0 | | 7x-12=15-4x | | 8x-(x-4)=7x | | =6P+540 | | y^2-2y-35= | | 4t-2= | | x+18+4x=-10-4x-17 | | t^2-8t=19 | | 58=-8(8m+5)-3-m+8 | | -7x+3y=38 | | 2x-(x+2)=-4 | | 19-x=14 | | 2(4-7)= | | 9t-6t+t-2= | | -109+x=34+12x | | -6-13=5x+18-4x | | 78=3(x)+18 | | 12c-15=11 | | 13*2+3= | | x=2y+2z+24 | | (3-u)(2u+9)=0 | | 8-5+3-4= | | Y=3x^3-2x^2-12x+8 | | 6x+25=74 | | Y=3x^2-2x^2-12x+8 | | (2v-7)(1-v)=0 | | 22y-198x=110 |